Thermal behaviour of different non-ionic surfactant concentration on the polymeric membrane - Abdul Rahman, Hassan; Badrulhaswan, B.; Ali, K.; Redhwan, A.A.M.; Nasir, A. (2021)
The principal objective of a study is indeed a well-functioning membrane such as high reject efficiency and high flow rate. In fact, too many studies are carried out on factors influencing the membrane, such as pressure intensity, polymer form, additive type, temperature influence during processing, and so on. Therefore, the study of thermal behaviour of surfactant concentration is vital to study the glass transition effect in good membrane production. Therefore, in this study, the main objective is to analyse the morphology structural effect of TX 100 surfactant on membrane by FTIR spectrum, and also to evaluate the thermal behaviour of different concentration of surfactant on membrane using DSC analysis. In order to study the thermal behaviour, membrane with 0, 1, 3 and 5 wt% was prepared. The effects of TX 100 concentration on membrane and thermal analysis have been studied and discussed. Membrane without TX 100 has 30 °C of glass transition temperature (Tg) while membrane with 5 wt% TX 100 has the highest Tg among the membranes. Therefore, the addition of surfactant to the membrane has an effect on Tg, thereby also impacting the porosity.